2021
DOI: 10.1126/sciimmunol.abg3533
|View full text |Cite
|
Sign up to set email alerts
|

Hobit identifies tissue-resident memory T cell precursors that are regulated by Eomes

Abstract: Hobit-expressing effector CD8 + T cells are T RM precursors, whose formation is regulated by the T-box transcription factor Eomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
55
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(60 citation statements)
references
References 75 publications
5
55
0
Order By: Relevance
“…In T cells, Eomes suppresses the formation of T RM precursors and T RM through Hobit downregulation, acting as a key TF for the regulation of lineage choice between circulating and resident memory T cells. [54] In contrast, T-bet overexpression results in increased expression levels of Hobit compared with controls. Therefore, Hobit is negatively and positively regulated by Eomes and T-bet in CD8 + T cells, respectively.…”
Section: Control Of Tissue Residency Versus Traffickingmentioning
confidence: 98%
See 1 more Smart Citation
“…In T cells, Eomes suppresses the formation of T RM precursors and T RM through Hobit downregulation, acting as a key TF for the regulation of lineage choice between circulating and resident memory T cells. [54] In contrast, T-bet overexpression results in increased expression levels of Hobit compared with controls. Therefore, Hobit is negatively and positively regulated by Eomes and T-bet in CD8 + T cells, respectively.…”
Section: Control Of Tissue Residency Versus Traffickingmentioning
confidence: 98%
“…Therefore, Hobit is negatively and positively regulated by Eomes and T-bet in CD8 + T cells, respectively. [54] Moreover, T-bet and Eomes ChIP-seq experiments identified peaks at the Hobit locus suggesting that this regulation was a direct activity of Eomes and T-bet [54,55] . Similar binding peaks at Hobit locus were also identified in NK cells.…”
Section: Control Of Tissue Residency Versus Traffickingmentioning
confidence: 99%
“…However, how and when Hobit and Blimp-1 instruct the branching off of Trm from terminal effectors and circulating memory T cells upon infection remains unresolved. Expression of Hobit appears highly restricted to the Trm lineage and allows for the unequivocal identification of Trm precursors [17,22]. In contrast, Blimp-1 is broadly expressed in antigen-experienced T cells and promotes terminal differentiation of effector CD8 + T cells besides instructing Trm formation [8,9,22].…”
Section: Introductionmentioning
confidence: 99%
“…Runx3 plays a primary role in CD8 + T RM differentiation by enhancing the expression of core residency signature and repressing the expression of signature genes of T CM ( 30 , 31 ). Downregulation of T-box transcription factor Eomes and T-bet is also necessary for early-stage T RM differentiation ( 32 , 33 ). Recent studies have found that effector-like and memory-like CD8 + T RM subsets can be distinguished by differential expression of two transcriptional factors Blimp-1 and Id3.…”
Section: T Rm In the Intestinementioning
confidence: 99%